Innovation Practices and External Support for MSME Performance and Survival in Indonesia - Pauline Henriette Pattyranie Tan; Martinus Tukiran; Dewi Wuisan (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
Amidst the rapid development of the digital economy, innovation practices are critical for enhancing performance and ensuring the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. As the backbone of the national economy, contributing significantly to GDP and employment, MSMEs are vital for macroeconomic resilience and inclusive growth. However, they consistently encounter systemic challenges in maintaining business performance and long-term survival, particularly within highly competitive and volatile markets, exacerbated by the aftermath of the COVID-19 pandemic. This study aimed to analyze the impact of innovation practices on MSME business performance and survival in Indonesia, with external support serving as a moderating factor. Using a purposive sampling technique, data was collected from 281 MSME actors in Jabodetabek who had embraced innovation. SEM-PLS analysis revealed that innovation practices positively and significantly affect both business performance and survival. Interestingly, external support did not moderate the influence of innovation practices on business performance but did moderate its effect on business continuity.